A highly threatened new species of Vanilla from Costa Rica - Karremans Lok, Adam Philip (2018)
A new species of Vanilla is described and illustrated from the southeastern tip of Costa Rica, close to the border with Panama. Vanilla karenchristianae was found in a region of the country that has no protected areas and very little original forest cover. The unexpected discovery highlights the importance of continued and sustainable conservation efforts across all life zones and ecoregions, underlining the importance of the public sector in biodiversity research and protection. The new species belongs to subgenus Xanata, which includes all the fragrant Vanilla species used in commerce. Vanilla karenchristianae is easily distinguished from all other Central American species by the combination of very narrow leaves, with a recurved apex, the green-and-white flowers and the appendages on the lip, a feature found otherwise only in the closely related Vanilla helleri, Vanilla insignis and Vanilla odorata.